Strategic intervention to enhance planning capability of barangay development councils in the Municipality of Anini-y, Antique, Philippines - Mosquera, Teopisto Jr. C. (1994)
Looking forward to the upliftment of Barangay Development Councils (BDCs) in the Municipality of Anini-y, Antique, this study will provide development planners guides and ideas on how to enhance planning capability of BCDs. Several programs and projects are identified to answer the needs of development councils in formulating responsive and effective development plans. The main objective of this study is to assess and institutionalize capability of the Barangay Development Councils in participatory and comprehensive development planning. As defined in the mandates of 1991 New Local Government Code each local government unit shall have a comprehensive multi-sectoral development plan to be initiated by its development council and approved by its Sanggunian. To be responsive, it is necessary that every BDC will be equipped with knowledge and skills in obtaining barangay development plans accordingly. SWOT Analysis is the tool adapted for analyzing the environment and to generate strategic options. In a matrix format strengthens and weaknesses of the BDCs where identified as well as he opportunities and threats prevailing in the external environment of the BDCs. This study had found out that almost all barangay officials have very low educational attainment such as some are only elementary graduates, a number have not finished high school and others still have finished only high school education. A big number of official were only marginal farmers and fishermen, thus they earn very meager income. hence, their planning capability is not thoroughly harnessed. To enhance capability of Barangay Development Councils in the development planning the following strategies are recommended: 1. improved literacy of barangay officials/BDCs; 2. BDC reorganization/activation; 3. increase income of BFC members; 4. improve data banking system; 5.enhance capability on barangay development planning; 6. strengthen organizations of barangay officials/BDcs; 7. intensify local leadership; and 8. expand linkages to GOs and NGOs.
Field Study report (Master of Management - RDM). -- [Iloilo City] : UPV-CM, November 1994.